2005
DOI: 10.1101/gad.1284605
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Polycomb-mediated repression of Hox genes requires the essential spliceosomal protein Sf3b1

Abstract: Polycomb group (PcG) proteins are responsible for the stable repression of homeotic (Hox) genes by forming multimeric protein complexes. We show (1) physical interaction between components of the U2 small nuclear ribonucleoprotein particle (U2 snRNP), including Sf3b1 and PcG proteins Zfp144 and Rnf2; and (2) that Sf3b1-heterozygous mice exhibit skeletal transformations concomitant with ectopic Hox expressions. These alterations are enhanced by Zfp144 mutation but repressed by Mll mutation (a trithorax-group ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 27 publications
9
107
2
Order By: Relevance
“…Recent studies have suggested that spliceosomal proteins participate in cellular functions besides the original splicing function. Heterozygote mice of SF3b subunit 1 (another U2 small nuclear ribonucleoprotein component) knock-out exhibited various skeletal alterations along the anterior-posterior axis, with altered expression of Hox genes, and heterozygotes of SF3b subunit 2 display similar skeletal abnormality (40). Although these studies support our findings, the detailed mechanisms by which SF3b4 regulates the cell surface BMPRI-A remain to be elucidated.…”
Section: Discussioncontrasting
confidence: 42%
“…Recent studies have suggested that spliceosomal proteins participate in cellular functions besides the original splicing function. Heterozygote mice of SF3b subunit 1 (another U2 small nuclear ribonucleoprotein component) knock-out exhibited various skeletal alterations along the anterior-posterior axis, with altered expression of Hox genes, and heterozygotes of SF3b subunit 2 display similar skeletal abnormality (40). Although these studies support our findings, the detailed mechanisms by which SF3b4 regulates the cell surface BMPRI-A remain to be elucidated.…”
Section: Discussioncontrasting
confidence: 42%
“…GEP of MDS patients show HOX deregulation with high risk of transformation to AML 98 and that HOX upregulation is associated with poor prognosis AML, 99 although no study has yet correlated the deregulation of HOX genes with SF3B1 mutations. However, the study in mouse 97 shows that SF3B1 spliceosomal protein is required to repress HOX genes, so there may well be a link between these two genes in the context of human disease, as predicted by the mouse model.…”
Section: Spliceosomal Mutationsmentioning
confidence: 99%
“…93 Pro-apoptotic profile in young mice reduced levels of transcripts and protein exhibiting skeletal alterations with associated changes in ectopic homeobox transcription factor HOX gene expressions in the vertebrae of embryos, leading to the conclusion that SF3B1 mediates repression of HOX genes. 97 HOX gene abnormalities have been implicated in fusions giving rise to myeloid malignancies, as described below. GEP of MDS patients show HOX deregulation with high risk of transformation to AML 98 and that HOX upregulation is associated with poor prognosis AML, 99 although no study has yet correlated the deregulation of HOX genes with SF3B1 mutations.…”
Section: Spliceosomal Mutationsmentioning
confidence: 99%
“…Sf3b1-knockout mice exhibit a homeotic phenotype that has been suggested to be linked to Polycomb repressive complex activity. 18 In line with the above observations, it was recently demonstrated that hematopoietic stem/progenitor cells from patients with CLL were capable of generating clonal B cells with a CLL-like phenotype, thus implicating hematopoietic stem/progenitor cells www.nature.com/leu in the pathogenesis of CLL, a mature lymphoid malignancy. 19 Similarly, TET2 mutations are found in both myeloid and lymphoid malignancies and in both instances, the mutations may be present in myeloid progenitors, again suggesting a stem cell origin for some mature lymphoid malignancies.…”
Section: Sf3b1 Mutationsmentioning
confidence: 66%
“…35,36 Some of these effects might involve direct recruitment of splice factors by chromatin mark readers, as has been shown for MRG15 (also known as MORF4L1) binding to H3K36me3 and recruitment of the polypyrimidine tract-binding protein to the nascent mRNA. 37 The lack of SF3B1 may impair PRC1 function 18 and the SPT3-TAFII31-GCN5L acetylase complex may also interact with splice factors. 38 Mutations affecting 'splice genes' may therefore alter either upstream the efficiency of transcription or downstream the kinetics of mRNA export to the cytoplasm and/or lead to RNA degradation.…”
Section: Sf3b1 Mutationsmentioning
confidence: 99%